2010
DOI: 10.1021/jp103131r
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Stable BOBO-3 H-Aggregate Complexes Hinders DNA Hybridization

Abstract: In recent works, we have been studying the photophysics and binding properties of the trimethine cyanine homodimer dye BOBO-3, a DNA intercalative fluorophore that shows an important fluorescence enhancement upon binding to double-stranded DNA. During the course of studying the interactions of the dye with single-stranded homo-oligonucleotides we detected the apparition of an additional absorption band centered on 466 nm. The large hypsochromic effect and the fact that direct excitation of this band resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 61 publications
3
21
0
Order By: Relevance
“…Direct covalent binding of dyes to DNA enables (i) choice of the type of dye, , (ii) choice of the number of dyes, , including assembly into large two- and three-dimensional (3-D) dye aggregate arrays, and (iii) the precise positioning of the dyes along the DNA backbone, ,, , which confers control over their spatial arrangement. Numerous studies have demonstrated exciton delocalization in dye aggregates templated within dsDNA structures, , even within more complex, higher-order DNA nanostructures. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct covalent binding of dyes to DNA enables (i) choice of the type of dye, , (ii) choice of the number of dyes, , including assembly into large two- and three-dimensional (3-D) dye aggregate arrays, and (iii) the precise positioning of the dyes along the DNA backbone, ,, , which confers control over their spatial arrangement. Numerous studies have demonstrated exciton delocalization in dye aggregates templated within dsDNA structures, , even within more complex, higher-order DNA nanostructures. , …”
Section: Introductionmentioning
confidence: 99%
“…Among the many types of dyes employed in DNA-templated aggregation, , cyanine dyes, a well-known group of a broader family of polymethine dyes, have established a particular prominence. Of especial note is the commercially available cyanine dye Cy5 (Figure a), which is a pentamethine dye that exhibits an intense absorption profile in the visible (specifically, the red) part of the electromagnetic spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…For these three possible cases, the allowed transitions are indicated by solid black arrows, while the forbidden transitions are indicated by dashed arrows in Figure . H-type aggregates exhibit a blue-shifted absorbance peak relative to the monomer, significantly reduced fluorescence emission intensity due to an optically forbidden energy transition from the lower energy exciton excited state (E – ), and a large Stokes shift. , , Conversely, J-type aggregates, discovered by Jelley , and Scheibe, exhibit a red-shift in the absorbance relative to the monomer since the only allowed optical transition is to the E – state, which consequently produce a nearly resonant fluorescence emission (i.e., small Stokes shift) with a sharp, high-intensity emission peak. ,,,,, Oblique aggregates display band (i.e., Davydov) splitting of the absorbance spectrum in which optical transitions to both E – and E + are allowed and reflect a mix of H- and J-aggregate optical properties. ,,,, …”
Section: Introductionmentioning
confidence: 99%
“…Capitalizing on the modularity enabled by DNA self-assembly allows larger, more complex arrays and networks of precisely controlled dye aggregates (i.e., dye assemblies) to be realized. Though there have been many studies that demonstrate exciton delocalization in DNA-templated dye aggregation within linear duplex structures, ,, ,, , only a few studies have exploited DNA constructs of more complex geometry. Most of these have been limited to studies employing three-armed junctions for dye assembly, which have been constructed to explore light-harvesting complexes and excimer behavior. , In our recent work, we were able to facilitate and control the transition of Cy5 dimers templated within a linear DNA duplex structure to a Cy5 tetramer in a mobile 4-arm junction (i.e., 4AJ) structure, thereby inducing a change in exciton delocalization from J-type to H-type behavior .…”
Section: Introductionmentioning
confidence: 99%
“…Coherent exciton delocalization, the process by which excitons (i.e., electron–hole pairs) spread in a wavelike manner over spatially separated molecular dyes, is an intriguing phenomenon that has attracted the interest of quantum computational theorists for the role it might play in photosynthesis. Frenkel, Davydov, and Kasha pioneered the theoretical description of exciton delocalization within molecular crystals and aggregates. Exciton delocalization in dye aggregate systems has been shown to exhibit itself in a wide variety of optical phenomena, including Dicke superradiance, Davydov splitting, ,, and its more specific manifestations: J- and H-aggregate behavior, superquenching, , exchange narrowing, , superfluorescence, , resonance fluorescence, and excitonically coupled circular dichroism (EC-CD), , many of which depend strongly on the geometrical configuration of the dye aggregates. Shown in Figure , coherent coupling between two dyes results in a splitting of the excited state energy levels for which the allowed energy transitions, and thus optical properties are strikingly different depending on whether the dye molecules undergo head-to-tail stacking (referred to as J-aggregates, Figure a) or parallel stacking (referred to as H-aggregates, Figure b).…”
Section: Introductionmentioning
confidence: 99%